Zika virus infection studies with CD34+ hematopoietic and megakaryocyte‐erythroid progenitors, red blood cells and platelets. Issue 3 (22nd February 2020) - Roth, Hanna; Schneider, Lucas; Eberle, Regina; Lausen, Jörn; Modlich, Ute; Blümel, Johannes; Baylis, Sally A.
Abstract : BACKGROUND: To date, several cases of transfusion‐transmitted ZIKV infections have been confirmed. Multiple studies detected prolonged occurrence of ZIKV viral RNA in whole blood as compared to plasma samples indicating potential ZIKV interaction with hematopoietic cells. Also, infection of cells from the granulocyte/macrophage lineage has been demonstrated. Patients may develop severe thrombocytopenia, microcytic anemia, and a fatal course of disease occurred in a patient with sickle cell anemia suggesting additional interference of ZIKV with erythroid and megakaryocytic cells. Therefore, we analyzed whether ZIKV propagates in or compartmentalizes with hematopoietic progenitor, erythroid, and megakaryocytic cells. METHODS: ZIKV RNA replication, protein translation and infectious particle formation in hematopoietic cell lines as well as primary CD34 + HSPCs and ex vivo differentiated erythroid and megakaryocytic cells was monitored using qRT‐PCR, FACS, immunofluorescence analysis and infectivity assays. Distribution of ZIKV RNA and infectious particles in spiked red blood cell (RBC) units or platelet concentrates (PCs) was evaluated. RESULTS: While subsets of K562 and KU812Ep6 EPO cells supported ZIKV propagation, primary CD34 + HSPCs, MEP cells, RBCs, and platelets were non‐permissive for ZIKV infection. In spiking studies, ZIKV RNA was detectable for 7 days in all fractions of RBC units and PCs, however, ZIKV infectious particles were not associated with erythrocytes or platelets. CONCLUSION: Viral particles from plasma or contaminating leukocytes, rather than purified CD34 + HSPCs or the cellular component of RBC units or PCs, present the greatest risk for transfusion‐transmitted ZIKV infections.